Thermal stability and plasmonic photothermal conversion of surface-modified solar nanofluids: Comparing prolonged and cyclic thermal treatments. (15th September 2021) - Sharaf, Omar Z.; Rizk, Nahla; Munro, Catherine J.; Joshi, Chakra P.; Waheed, Waqas; Abu-Nada, Eiyad; Alazzam, Anas; Martin, Matthew N.
Highlights: Gold nanoparticles (AuNPs) thermally stabilized by natural/synthetic polymer shells. Thermal stability of four plasmonic solar nanofluids thoroughly investigated. The heating mode (continuous or cyclic) found to play a critical role in stability. PVP most suitable as protectant shell for AuNPs in solar photothermal applications. Optical/thermal simulations of nanofluid-based direct-absorption solar collectors. Abstract: In this work, the thermal stability of plasmonic nanofluids upon continuous and cyclic heating and cooling for different durations and temperatures was investigated for volumetric-absorption solar applications. Gold nanoparticles (AuNPs) capped with citrate (CIT) were compared to polymer-protected AuNPs coated using physical/chemical adsorption with natural bovine serum albumin (BSA) or synthetic polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP) polymers. Evaluation of post-test stability and identification of possible failure modes were realized using complementary characterization techniques. Furthermore, simulations were used to gain insight on the effects of nanofluid stability on the optical and thermal performance of direct-absorption solar collectors (DASCs). All nanofluid types retained their dispersion stability after long-term aging for 3 + years. For the first time, to our knowledge, the heating mode (whether cyclic or continuous), not just the heating temperature and duration, was found to play a critical role in determining the effects on dispersion stability, physicochemical coating transformations, optical properties, and wettability of nanofluids. This emphasized the importance of testing solar nanofluids using thermal stability tests that mimicked the cumulative failure modes induced by diurnal solar cycling. The impact of prolonged and cyclic heating was found to vary from excessive aggregation, weakened polymer-Au linkage, and reduced polymer–solvent affinity, depending on the AuNP coating. Overall, PVP was found most suitable as a soft protectant shell for plasmonic nanoparticles in solar photothermal applications. This work represents an important step towards the commercial use of photothermally efficient yet colloidally stable solar nanofluids capable of retaining their superior properties in field deployments.